?P VE BVP DİZİ UZAYLARINDA B(R,S) VE B(R,S,T) OPERATÖRLERİNİN İNCE SPEKTRUMLARI - ÖZALTIN, BURCU (Fırat Üniveristesi, 2012)
Bu çalışma dört bölümden oluşmaktadır. İlk bölümde; bazı temel kavramlar verilmiştir. İkinci bölümde; spektral teori hakkında bilgiler verilmiştir. Üçüncü bölümde; ve bvp dizi uzayları üzerinde B(r,s) operatörünün ince spektrumu kavramı verilmiştir. Dördüncü bölümde; ve bvp dizi uzayları üzerinde B(r,s,t) operatörünün ince spektrumu kavramı verilmiştir.Anahtar Kelimeler: Bir operatörün spektrumu, ve bvp dizi uzayları, Fark operatörü, Genelleştirilmiş fark operatörü.

On The Fine Spectrum of The Difference Operators B(r,s) and B(r,s,t) Over The Sequence Spaces ?p and bvpThis thesis consists of four chapters. In the first chapter some fundamental notions were given. In the second chapter some information about spectral theory were given. In the third chapter the fine spectrum of the difference operator B(r,s) over the sequence spaces and bvp were given. In the four chapter the fine spectrum of the difference operator B(r,s,t) over the sequence spaces and bvp were given.Key Words : Spectrum of an operator, The sequence spaces and bvp, Difference operator, Generalized difference operator.
On the fine spectrum of the difference operators B(r,s) and B(r,s,t) over the sequence spaces ?p and bvp
Keywords: Matematik